Chinese Computational Linguistics and Natural Language Processing Based on Naturally Annotated Big Data 12th China National Conference, CCL 2013 and First International Symposium, NLP-NABD 2013, Suzhou, China, October 10-12, 2013, Proceedings - Sun, Maosong; Zhang, Min; Lin, Dekang; Wang, Haifeng (Lecture Notes in Artificial Intelligence,, 2013)
This book constitutes the refereed proceedings of the 12th China National Conference on Computational Linguistics, CCL 2013, and of the First International Symposium on Natural Language Processing Based on Naturally Annotated Big Data, NLP-NABD 2013, held in Suzhou, China, in October 2013. The 32 papers presented were carefully reviewed and selected from 252 submissions. The papers are organized in topical sections on word segmentation; open-domain question answering; discourse, coreference and pragmatics; statistical and machine learning methods in NLP; semantics; text mining, open-domain information extraction and machine reading of the Web; sentiment analysis, opinion mining and text classification; lexical semantics and ontologies; language resources and annotation; machine translation; speech recognition and synthesis; tagging and chunking; and large-scale knowledge acquisition and reasoning.